Research on Institutional Invalidation Caused by "Potential Rules". (July 2020) - Wang, Yu; Tao, Ding
Abstract: Through the simulation study of multi-equilibrium game with "Potential Rule" strategy, we find that the behaviour of "Potential rule" can be evolved through repeated game without considering any other social preferences of the subject and any prior knowledge of the game. This paper will analyse the endogenous evolution of the third strategy, namely the "Potential Rules", between the choices of fair and unfair strategies from the perspective of interest transmission. The experimental results show that the subjects who own the third strategy with the characteristics of "Potential Rules" will spread to other subjects in a certain institutional environment by imitating learning and adjusting strategies. The third strategy will become a guide to the behaviour of the subjects and form a deviation of the institution, which will lead to institutional failure.